2015
DOI: 10.1002/cpt.110
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the public health impacts of legalizing recreational cannabis use in the USA

Abstract: Background and aims

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
129
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 51 publications
0
129
0
5
Order By: Relevance
“…Some States in the US have shifted their policy stance to permit use of cannabis for therapeutic purposes (CTP) (Chu, 2014). This legalisation in the form of de facto supply for medical use has not caused increased consumption, prevalence of use or related adverse consequences (Nussbaum, Boyer & Kondrad, 2011;Hall & Weier, 2015;Sznitman and Zolotov, 2015;Ziemianski, Capler, Tekanoff , Lacasse, Luconi & Ware, 2015) and according to one study has contributed to heightened patient perceptions of safety and awareness (Trout & DiDonato, 2015). (Ebert, Zolotov, Eliav, Ginzburg, Shapira & Magnezi, 2015), with Israeli rheumatologists observing a majority opinion for the role of cannabinoids in the management of rheumatoid disease (Ablin, Elkayam & Fitzcharles, 2016).…”
mentioning
confidence: 99%
“…Some States in the US have shifted their policy stance to permit use of cannabis for therapeutic purposes (CTP) (Chu, 2014). This legalisation in the form of de facto supply for medical use has not caused increased consumption, prevalence of use or related adverse consequences (Nussbaum, Boyer & Kondrad, 2011;Hall & Weier, 2015;Sznitman and Zolotov, 2015;Ziemianski, Capler, Tekanoff , Lacasse, Luconi & Ware, 2015) and according to one study has contributed to heightened patient perceptions of safety and awareness (Trout & DiDonato, 2015). (Ebert, Zolotov, Eliav, Ginzburg, Shapira & Magnezi, 2015), with Israeli rheumatologists observing a majority opinion for the role of cannabinoids in the management of rheumatoid disease (Ablin, Elkayam & Fitzcharles, 2016).…”
mentioning
confidence: 99%
“…Any immediate effects of legalization on adolescent uptake and use may be modest [9]. It will take time for a legal industry to scale up to meet the demand from existing adult users and these States have also initially restricted the number of legal sellers to make it easier to regulate an emerging industry.…”
mentioning
confidence: 99%
“…26 Regional analyses showed that the rates are not increasing uniquely in those states where legalization has been instituted, suggesting that the changes are not driven solely by the revised legal status. 27,28 Cannabis use disorders increased in these regions also, but less steeply than rates of use. 26 Does cannabis legalization increase the likelihood of children using cannabis?…”
Section: Cannabis Use and The Lawmentioning
confidence: 99%